Attitudes to and experiences of intimate partner violence among Rohingya women who married before eighteen years of age - M. Mofizul Islam; Md Nuruzzaman Khan; Md Mashiur Rahman (Global Health Action)
Currently, around a million Rohingya refugees live in Cox’s Bazar, Bangladesh. This study examines the attitudes toward physical abuse and experiences of intimate partner violence (IPV) of Rohingya refugee women who experienced child marriage. A cross-sectional survey was conducted in the Rohingya refugee settlement at Cox’s Bazar, Bangladesh. Attitudes towards physical abuse have been assessed by a set of five questions that asked the situation under which ‘hitting or beating’ one’s wife is justifiable. Multivariable logistic regressions are used to examine the associations of exposure to child marriage with (i) attitudes towards the justification of physical abuse by one’s husband and (ii) experiences of IPV in the 12 months prior to the survey. Data are available for 486 participants. Overall, 61.32% of women experienced child marriage (married before 18 years of age) and they were more likely to have strongly justified beatings/hitting one’s wife under certain circumstances (Adjusted Odds Ratio (AOR) = 2.71; 95%CI: 1.78, 4.11), and to have experienced such IPV by their husbands in the 12 months prior to the survey (AOR = 1.72; 95%CI: 1.13, 2.61). These AORs are higher for women married at ages 12–14 than those married at 15–17. Having some formal education among husband and wife is protective of abuse within a marriage. Rohingya women’s attitudes towards and experiences of IPV are associated with their exposure to child marriage. Interventions for stopping child marriage, marriage registration, social support group, and legal interventions are needed. Offering formal education to all children needs to be prioritized.